A duplex sequencing approach for high-sensitivity detection of genome-edited plantsEuropean Nucleotide Archive (ENA) at EMBL-EBI - Laura Bonfini; Moreno Colaiacovo; Cristian Savini; Christoph von Holst; Matteo Maretti; Francesco Gatto; Federica Magni; Paloma Pérez-Bello; Davide Scaglione (Food Chemistry: Molecular Sciences, 2025)
In this paper, we have evaluated a targeted high-throughput massive parallel sequencing approach for detecting single nucleotide mutations or small genomic changes generated by new genomic techniques (NGT).We used unique molecular identifiers (UMIs) for the quantification of the mutant alleles and duplex sequencing to confirm a mutation on both strands to avoid polymerase chain reaction (PCR) artefacts or sequencing miss-calls. We tested the approach in blinded analyses on a set of mixed NGT-modified tomato lines and identified each single nucleotide mutation or small insert/deletion (InDel) down to a 0.1 % level. To our knowledge, this is the first performance evaluation of a duplex sequencing approach for detecting and quantifying small NGT DNA changes without a priori knowledge of the mutation type and position in a target region.Our study advances the scientific discussion on detecting NGT-induced DNA modifications in plants and food products, evaluating the potential and current limitations of a cutting-edge NGS-approach.